The Malaysian Islamic Party PAS 1951-2013 Islamism in a mottled nation - Farish A. Noor (Farish Ahmad Noor) 1967- (Strategic Information and Research Development Centre, 2016)
The Pan-Malaysian Islamic Party (PAS) is the biggest opposition party in Malaysia and one of the most prominent Islamist parties in Southeast Asia. Tracing its development from 1951 to the present, this ambitious study explains how PAS acquired both local and international relevance. Farish A. Noor charts the party's rise alongside the different ideological postures - from anticolonialism to postrevolutionary Islamism - that it has adopted over the years. Exploring how PAS has continuously adapted to contemporary realities, he makes an important contribution to our understanding of Malaysia's Islamist movement, as well as the country's broader political history